Pengaruh Perputaran Modal Kerja Dan Perputaran Piutang Terhadap Profitabilitas Pada PT. Hanjaya Mandala Sampoerna Tbk - Mardiah; Nafisah Nurulrahmatiah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
This study aims to determine how much influence the working capital turnover and accounts receivable turnover on profitability at PT. Hanjaya mandala Sampoerna Tbk. The research used is through the descriptive and verification method approach where the results of the study indicate that the size of the working capital turnover and accounts receivable turnover have a contribution to profitability.